2016
DOI: 10.3748/wjg.v22.i40.8956
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine neoplasms of liver - A 5-year retrospective clinico-pathological study applying World Health Organization 2010 classification

Abstract: AIMTo study the clinicopathological characteristics of neuroendocrine neoplasms (NEN) on liver samples and apply World Health Organization (WHO) 2010 grading of gastroenteropancreatic (GEP) NEN.METHODSClinicopathological features of 79 cases of NEN of the liver diagnosed between January 2011 to December 2015 were analyzed. WHO 2010 classification of GEP NEN was applied and the tumors were graded as G1, G2 or G3. Two more categories, D1/2 (discordant 1/2) and D2/3 (discordant 2/3) were also applied. The D1/2 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Neuroendocrine tumors (NETs), mostly originating from bronchopulmonary and gastrointestinal sites, are uncommon low-malignancy tumors that affect 6.98/100000 individuals annually, however, the incidence rate was in upward trend from 2000 to 2014 worldwide[ 1 , 2 ]. According to the World Health Organization 2019 classification of gastroenteropancreatic NETs, NETs are divided into four grades: NET G1 (low grade), NET G2 (intermediate grade), NET G3 (high grade), and neuroendocrine carcinomas (NEC), based on mitotic count and Ki-67 index of the tumor[ 3 , 4 ]. More than 80% of hepatic NETs are metastatic for the dual blood supply to the liver provides an advantage for tumor metastasis to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs), mostly originating from bronchopulmonary and gastrointestinal sites, are uncommon low-malignancy tumors that affect 6.98/100000 individuals annually, however, the incidence rate was in upward trend from 2000 to 2014 worldwide[ 1 , 2 ]. According to the World Health Organization 2019 classification of gastroenteropancreatic NETs, NETs are divided into four grades: NET G1 (low grade), NET G2 (intermediate grade), NET G3 (high grade), and neuroendocrine carcinomas (NEC), based on mitotic count and Ki-67 index of the tumor[ 3 , 4 ]. More than 80% of hepatic NETs are metastatic for the dual blood supply to the liver provides an advantage for tumor metastasis to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only 5%-10% of diagnosed patients are eligible for resection with a risk of extremely high recurrence rates. It was reported that 94% of patients will relapse within 5 years (6,7). Metastasis usually occurs in the prophase of NETs.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Immunohistochemically, most PHNET cases were reported to be strongly positive for CgA (67-100%) and Syn (92-100%). 5,[13][14][15] Several pieces of literature provided detailed serum AFP level in PHNET patients, mostly in normal range from 1.2 to 4.8 ng/mL, only one case with highly elevated AFP of 7397 IU/mL (8950 ng/mL). 7,13,15 Notably, the PHNET case with significant AFP elevation showed a high tumor grade of G3 and a poor prognosis with 0.7-month survival, but no further mechanism analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…5,[13][14][15] Several pieces of literature provided detailed serum AFP level in PHNET patients, mostly in normal range from 1.2 to 4.8 ng/mL, only one case with highly elevated AFP of 7397 IU/mL (8950 ng/mL). 7,13,15 Notably, the PHNET case with significant AFP elevation showed a high tumor grade of G3 and a poor prognosis with 0.7-month survival, but no further mechanism analysis was performed. 15 Another differential diagnosis in this case is HCC with neuroendocrine component or mixed tumor of HCC and NEC.…”
Section: Discussionmentioning
confidence: 99%